(untitled) (Applied Biological Research, 2011)
Histochemical studies of carbohydrates and proteins were conducted on the trachea of ten adult healthy Black Bengal goats (Capra hircus) of either sex. The goblet cells, tracheal glands and tracheal cartilages manifested intense positive reactions generally for carbohydrates, whereas connective tissue and muscle fibres were weak to moderately positive for these constituents. The epithelium, glands, cartilage matrix, perichondrium and muscle layers manifested strong reactions for acid mucopolysaccharides. Reaction for proteins was strong to intense in the epithelium, glands, perichondrium and muscle fibres, whereas other structures showed only weak or moderate reaction.